PENGARUH STRES KERJA, KEDISPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Dinus Roy Mentegau, 07.05.51.0144; Sutomo, Yohanes (Students Journal of Economic and Management, 2012)
Employees who have a good performance orachievement isthe hopeof everycompany. Good performancecan beachieved ifavoid stress, discipline, andthe motivation of the employer. The purpose of this study was to analyze thesig ni ficanteffects of job stress, discipline, and motivation either partiallyor simultan eouslyand toanalyze the dominant independent variables and their effects onemployee performance staff. The research methodis a survey. The type of databeing usedis qualitative and quantitative. Source of data used is primary data and secondary data. The population was amounted to 109 employees staff employees. Samples take namounted to 33 respondents. Testinstrumentsusing the validity and reliability. Data analysis techniques using multiple linear regression, t test, F test and the coefficient of determination. Advicecan begiven leaderships hould increase motivationby providing hope, and incentives to employees to bemore vibrantworks. Corporate leaderss houldresolveas early as possible or keepthings that canlead tojob stress, with thecamdid not provide atough work load and excessive, and to provide remunerationis not toolow. And leaders should further enhance the discipline factorth at better employee performance, discipline by setting preventive, corrective and progressive discipline discipline. Key words: job stress, discipline, motivation, and employee performance.